Effects of the good behavior game across classroom contexts. Issue 1 (10th October 2016) - Pennington, Brittany; McComas, Jennifer J.
Abstract : The Good Behavior Game (GBG), a well‐researched classroom group contingency, is typically played for brief periods of time, which raises questions about the effects on subsequent contexts. This study used a multiple baseline design and showed that when the GBG was implemented in one context, behavior improved in only that context. Behavior improved in the subsequent activity only when the GBG was implemented.